Catalytic Effect of Pd-Ni Bimetallic Catalysts on High-Temperature Co-Electrolysis of Steam/CO2 Mixtures - Kim, Si-Won; Park, Mansoo; Kim, Hyoungchul; Yoon, Kyung Joong; Son, Ji-Won; Lee, Jong-Ho; Kim, Byung-Kook; Lee, Jong-Heun; Hong, Jongsup (ELECTROCHEMICAL SOC INC, 2016)
The performance of solid oxide electrolysis cells for high-temperature co-electrolysis of steam/CO2 mixtures was enhanced by raising the amount of Pd-Ni bimetallic catalysts fabricated inside their fuel-electrode substrate. High-temperature co-electrolysis has been proposed as a promising technology to store renewable electrical energy in the form of chemical energy and convert CO2 to valuable syngas. To deploy it into energy markets, it is essential to improve its energy storage efficiency and syngas productivity. In this study, the catalytic effect of Pd-Ni bimetallic catalysts on electrochemical performance and CO2 conversion was examined to meet these needs. Their homogeneous morphology and distribution were obtained by using an advanced infiltration technique. Increasing the amount of Pd-Ni bimetallic catalysts promotes a reverse water gas shift (RWGS) reaction enhancing steam transport toward the functional layer and hence decreasing a concentration overpotential. This raises a limiting current density and reduces an overvoltage imposed on the cells, in particular, at high current density. In addition, the enhanced RWGS reaction kinetics driven by a higher amount of Pd-Ni bimetallic catalysts loadings enables increasing the CO2 conversion rate and CO concentration in the product stream. These may enhance the energy storage capacity and lowers the energy requirements for high-temperature co-electrolysis. (C) 2016 The Electrochemical Society. All rights reserved.
Keywords: SOLID OXIDE CELLS; CARBON DEPOSITION; SYNGAS PRODUCTION; COMPOSITE ANODES; INFILTRATION; OXIDATION; METHANE; H2O; ELECTROCATALYSTS; ELECTROOXIDATION